Performance of real-time polymerase chain reaction and Kato-Katz for diagnosing soil-transmitted helminth infections and evaluating treatment efficacy of emodepside in randomized controlled trials. - Christian N Lotz; Emmanuel C Mrimi; Pierre H H Schneeberger; Said M Ali; Jan Hattendorf; Jennifer Keiser (PLoS Neglected Tropical Diseases)
Background The World Health Organization recommends the use of the microscopy-based Kato-Katz thick smear for diagnosing soil-transmitted helminth (STH) infections. Despite its simplicity and cost-effectiveness, the Kato-Katz method faces challenges, including reader subjectivity and reduced sensitivity. Real-time polymerase chain reaction (qPCR) technology offers standardized readouts and higher sensitivity, making it suitable for STH diagnosis and monitoring the treatment efficacy of emodepside within the framework of randomized controlled trials. Methodology/principal findings We evaluated the performance of Kato-Katz versus qPCR for assessing treatment efficacy in terms of cure rates, of single doses of 5, 10, 15, 20, 25 and 30 mg of emodepside compared to 400 mg albendazole. Spearman's rank correlation coefficient examined the correlation between STH eggs per gram in stool samples and qPCR Ct values. Diagnostic sensitivity of qPCR was calculated using a Bayesian latent class modelling approach with data from Ascaris lumbricoides infections. Agreement between Kato-Katz and qPCR at baseline was 93.57% for Trichuris trichiura, and 73.49% for both hookworm and A. lumbricoides. For the latter helminth qPCR demonstrated higher sensitivity (85.00% vs. 47.70%) and slightly lower specificity (93.40% vs. 99.40%) compared to Kato-Katz. We observed a fair to moderate agreement with negative correlation between Ct values and Kato-Katz egg counts. Treatment efficacy, as assessed by qPCR, was lower for all doses of emodepside and albendazole compared to Kato-Katz. Nonetheless, emodepside demonstrated higher cure rates against T. trichiura and A. lumbricoides infections compared to albendazole. Conclusion/ significance Our study confirmed that qPCR is a sensitive diagnostic method for diagnosing STH infections compared to Kato-Katz and serves as a valuable tool for determining treatment efficacy in clinical trials. Furthermore, qPCR confirmed the better treatment efficacy of emodepside compared to albendazole, despite indicating lower cure rates than Kato-Katz.